The Supreme Spectacle: An Analysis of Public Attendance at the Supreme Court. (1st November 2022) - Truscott, Jake S.
Abstract: While many are aware that the Supreme Court allocates seats for the public to view oral arguments, substantive analyses that have measured the motivations for attendance are lacking. I analyze who attends oral arguments using a descriptive approach with a novel dataset of public attendance at Supreme Court oral arguments during the 2019 term. A concurrent assessment of interviews conducted on argument days illustrates notable differences among the motivations of prospective attendees. I conclude by noting that although the linkage between latent case salience and the demand for admission to arguments is not neatly discernable, attendance at the Supreme Court offers an interesting divergence from perceptions of attendance in a traditional courtroom setting.